2020
DOI: 10.1080/19761597.2020.1865824
|View full text |Cite
|
Sign up to set email alerts
|

Does IoT service orchestration in public services enrich the citizens’ perceived value of digital society?

Abstract: The continuous growth of digital transformation aims to leverage the changes and opportunities for IoT technologies in public sector, which has created an impact on the sustainability of digital societies. The Internet of Things (IoT) contains significant challenges such as citizens' perceived value towards intention to use in public services that could stand in a way of realizing its potential benefits. Our study aims to investigate the influencing factors of citizens' usage intention concerning IoT service o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 92 publications
(133 reference statements)
0
13
0
2
Order By: Relevance
“…In addition, incentives can be provided for the use of the internet such as generous subsidies taking advantage of European fi nancial instruments. A readjustment of education focused on informatics can improve the public's use of digital services (Hu et al, 2020). Other policies that can be implemented in order to improve the e-government are the modernization of Greek legislation with technology, provision of open access information in an easy way, ensure use of the Internet for all citizens, reduction of illiteracy, the application of new technologies, ensure the participation of the public in the design and implementation of electronic services, ensure the ability to manage IT services, and simplifi cation of the use of electronic services (World Bank, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, incentives can be provided for the use of the internet such as generous subsidies taking advantage of European fi nancial instruments. A readjustment of education focused on informatics can improve the public's use of digital services (Hu et al, 2020). Other policies that can be implemented in order to improve the e-government are the modernization of Greek legislation with technology, provision of open access information in an easy way, ensure use of the Internet for all citizens, reduction of illiteracy, the application of new technologies, ensure the participation of the public in the design and implementation of electronic services, ensure the ability to manage IT services, and simplifi cation of the use of electronic services (World Bank, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The IoT will soon influence every aspect of society (Xu and Li, 2021), especially in academic libraries at higher education institutions. In this research study, we have employed the deductive approach in research method (Bryman and Bell, 2018), beginning with the conceptual theory and leading to research hypotheses (Collis and Hussey, 2014) which are confirmed or rejected (El-Haddadeh et al , 2019; Hu et al , 2020). There exist key reasons to adopt this approach in our research study, as this approach is appropriate for addressing recent or evolving issues that need initial conceptualization.…”
Section: Methodsmentioning
confidence: 99%
“…Assim, a intensificação e incorporação dos recursos da tecnologia da informação modificam a forma como os serviços públicos são prestados aos cidadãos (Carvalho Filho, 2017;Priisalu & Ottis, 2017;Ilindgren et. al., 2019;Hu, Chohan & Liu, 2022;Wu & Xiao, 2022).…”
Section: Serviços Públicos Digitaisunclassified